Retrospective analysis of reproductive health indicators in the United Nations High Commissioner for Refugees post-emergency camps 2007–2013. Issue 1 (December 2016) - Whitmill, Jennifer; Blanton, Curtis; Doraiswamy, Sathyanarayanan; Cornier, Nadine; Schilperood, Marian; Spiegel, Paul; Tomczyk, Barbara
Abstract Background The United Nations Refugee Agency's Health Information System issues analytical reports on the current camp conditions and trends for priority reproductive health issues. The goal was to assess the status of reproductive health by analyzing seven indicators and comparing them to standards and host country estimates. Methods Data on seven indicators were extracted from the database during a seven-year period (2007 through 2013). A standardized country inclusion criterion was created based on the year of country implementation and the percentage of missing reports per camp and year. The unit of analysis was monthly camp reports by year within a country. To account for the lack of independence of monthly camp reports, the variance was computed using Taylor Series Linearization methods in SAS. Results Ten of the 23 eligible countries met the inclusion criterion. The mean camp maternal and neonatal mortality rates, except for two country years, were lower than the host country estimates for all countries and years. There was a significant increase in the percent of births attended by a skilled birth attendant (p  < 0.0001), and 8 of 10 countries did not meet the standard of 100 % for all reporting years. The percent of births performed by Caesarian section (p  < 0.001), were below the recommended minimum standard for nearly half of the countries every year. There was a significant increase in the percent of women screened for syphilis across years (p  < 0.0001) and the percent of women who received post HIV exposure prophylaxis (p  < 0.0001) and 10 % reached the standard for all reporting years, respectively. Conclusion Comprehensive, consistent and comparable statistics on reproductive health provides an opportunity to assess progress towards indicator standards. Despite some improvements over time, this analysis confirms that most countries did not meet standards and that there were differences in reproductive health indicators between countries and across years. Consequently, the HIS periodic monitoring of key reproductive health indicators at the camp level should continue. Data should be used to improve intervention strategies.